(untitled) (Lebenswelt. Aesthetics and philosophy of experience., 2016)
Much of the philosophical attention directed to Kant’s intervention into biology has been directed toward Kant’s idea of a transcendental limit upon what can be understood constitutively. Kant’s own wider philosophical practice, however, was principally oriented toward solving problems and the scientific benefits of his methodology of teleology have been largely underappreciated, at least in the English language literature. This paper suggests that all basic biology has had, and continues to have, a need for some form of heuristic “bracketing” and that a renewal of some form of, albeit flexible, teleological methodological bracketing can better complement the productive assimilation into developmental biology of continuing advances in our understanding of the mesoscale physics and chemistry of soft, excitable condensed matter, than what has been the prevailing and de facto use of a form of bracketing shaped by the neoDarwinian Modern Synthesis. Further we offer a concept of biogeneric processes and a framework of physico-genetic “dynamical patterning modules”, that can begin to account for the appearance of new Kantian “stocks of Keime und Anlagen”, capable of potentiating some range of possible organismal forms, and provide grounds for moving up the teleological “goalposts”, i.e., expanding the range of what can be accounted for on a constitutive basis.